Incident retinal vein occlusions and estimated cerebrospinal fluid pressure. The Beijing Eye Study. (20th May 2015) - Jonas, Jost B.; Wang, Ningli; Wang, Ya Xing; You, Qi Sheng; Yang, Diya; Xie, Xiaobin; Xu, Liang
Abstract Purpose To examine whether the incidence of retinal vein occlusions (RVOs) is associated with estimated cerebrospinal fluid pressure (CSFP). Methods The population‐based Beijing Eye Study, which included 4439 subjects (age: 40 + years) in 2001, was repeated in 2011 with 2695 subjects participating (66.4% of the survivors). Fundus photographs were examined for the new development of RVOs, differentiated into central RVOs (CRVOs) and branch RVOs (BRVOs). CSFP was calculated as CSFP [mmHg] = 0.44 × Body Mass Index [kg/m2] + 0.16 × Diastolic Blood Pressure [mmHg]−0.18 × Age[Years]. Results Incident BRVOs were detected in 50 eyes and incident CRVOs in 8 eyes. BRVOs were located at arterio‐venous crossings in 39 eyes. In multivariate analysis, a higher estimated CSFP was associated with a higher incidence of CRVOs (p = 0.004; standardized coefficient beta: 0.06; regression coefficient B: 5.35; 95% confidence interval (CI):1.73, 8.96) after adjusting for urban region (p < 0.001; beta: −0.52; B: −3.93; 95% CI: −4.29, −3.57), higher educational level (p = 0.001; beta: 0.13; B: 0.44; 95% CI: 0.28, 0.60), higher blood concentrations of triglycerides (p < 0.001; beta: 0.08; B: 0.11; 95% CI: 0.05, 0.16) and higher intraocular pressure (p < 0.001; beta: 0.16; B:0.21; 95% CI: 0.16, 0.27). As a corollary, a higher incidence of RVOs as a whole, as well as a higher incidence of CRVOs combined with a higher incidence of BRVOs originating at the optic nerve head, both were significantly associated with higher estimated CSFP (p = 0.002; odds ratio (OR): 1.15; 95% CI: 1.05, 1.25; and p = 0.037; OR: 1.17; 95% CI: 1.01, 1.35, respectively) after adjusting for older age. Conclusions A higher estimated CSFP was associated with a higher incidence of RVOs originating at the optic nerve head (i.e. CRVOs, hemi‐central RVOs and BRVOs originating at the optic nerve head), and vice versa, a higher incidence of RVOs was associated with a higher estimated CSFP. It suggested an influence of higher estimated CSFP on higher central retinal vein pressure.